2014
DOI: 10.1038/ijos.2014.38
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic activity of Streptococcus mutans biofilms and gene expression during exposure to xylitol and sucrose

Abstract: The objective of the study was to analyse Streptococcus mutans biofilms grown under different dietary conditions by using multifaceted methodological approaches to gain deeper insight into the cariogenic impact of carbohydrates. S. mutans biofilms were generated during a period of 24 h in the following media: Schaedler broth as a control medium containing endogenous glucose, Schaedler broth with an additional 5% sucrose, and Schaedler broth supplemented with 1% xylitol. The confocal laser scanning microscopy (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
70
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(80 citation statements)
references
References 51 publications
10
70
0
Order By: Relevance
“…Our findings are similar to Shemesh et al (2006) and Decker et al (2014) who studied the effect of different carbohydrates. In addition to this, they investigated the expression of glucosyltransferases and other biofilmassociated genes and found that the combined presence of carbohydrates stimulate the upregulation of glucanand biofilm-associated genes in a different way than glucose alone.…”
Section: Discussionsupporting
confidence: 81%
“…Our findings are similar to Shemesh et al (2006) and Decker et al (2014) who studied the effect of different carbohydrates. In addition to this, they investigated the expression of glucosyltransferases and other biofilmassociated genes and found that the combined presence of carbohydrates stimulate the upregulation of glucanand biofilm-associated genes in a different way than glucose alone.…”
Section: Discussionsupporting
confidence: 81%
“…The latter fact suggests an inhibition of water-insoluble glucans synthesis because these polymers are essential for the biofilm development, and no glucans lead to no biofilm formation (3,16). It should be noted that, in the presence of sucrose, S. mutans adhesion to solid surfaces (e. g. glass, tooth enamel) is mainly dependent on the activity of glucosyltransferases, especially those synthesizing water-insoluble glucans (16)(17)(18). This was evidently demonstrated by Ooshima et al (16) using S. mutans GtfB/C-deficient mutant strains -their ability to adhere to the glass surface was significantly reduced in spite of the presence of sucrose within the medium.…”
Section: Discussionmentioning
confidence: 99%
“…Significant persistence of S. mutans under the acidic environment encourages the proliferation of S. mutans including other acidogenic bacteria, resulting in their ability to survive at a low-pH condition. Upon changing to the low-pH condition, the initiation of the dental caries starts under the surface of teeth covered with biofilm (Chen et al 2012;Decker et al 2014). Therefore, the potential acidification of dental biofilms and later cavity formations can be decreased by eliminating the adherence of S. mutans to the surface of teeth or dental biofilms.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to these features concerted with its survivability, natural bioactive substances such as sugar-alcohol, antocyanine, and specific sugars have been focused as potent antimicrobial materials. It has been implicated that extracellular water-insoluble polysaccharide from dietary sugar produced by dextransucrase (DSase) and its adhesion to dental enamel are known to the most clinically important biological abilities of S. mutans (Chen et al 2012;Decker et al 2014). However, the mechanisms under which this cariogenic pathogen can survive or proliferate under in such environmental conditions are so far largely unknown.…”
Section: Introductionmentioning
confidence: 99%